Effect of Celery (Apium graveolens L) Addition on Organoleptic Properties of Mocaf Flour-based Wonton Stuffing. - Rofendi, Hawa Auliya; Chusnah, Miftachul; Hartanti, Dyah Ayu Sri; Zuhria, Siti Aminatuz; Naim, Abu; Faizah, Mazidatul (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The use of wheat flour continues to dominate the Indonesian food industry despite growing dependency on imports. To reduce this reliance, mocaf (Modified Cassava Flour) offers a promising local alternative with similar characteristics to wheat flour. This study investigates the effect of adding celery (Apium graveolens L.) to the organoleptic properties of mocaf-based wonton filling, including aspects of color, aroma, taste, and texture. The research used a Completely Randomized Design (CRD) with three treatments: P (2 g celery), Q (4 g celery), and R (6 g celery) per 500 g dough. A descriptive qualitative method and ANOVA followed by LSD (Least Significant Difference) test were used for data analysis. Results showed that treatment R (6 g celery) yielded the most favorable sensory outcomes with color 4.60, aroma 5.12, taste 4.89, and texture 4.65. The addition of 6 g celery provided a distinctive green color, strong aroma, pleasant taste, and soft texture without mushiness, significantly improving the organoleptic properties (p<0.05).